The Wisdom of Local Communities in the Preservation of Subayang River Ecosystems at Tanjung Belit Kampar Kiri Sub District Hulu Kampar Regency Riau Province - Samsul Bahari; Kusai '; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research of The Wisdom of Local Communities in the Preservation of Subayang River Ecosystems was Conducted in April 2016 at Tanjung Belit village Kampar Kiri Sub District Hulu Kampar Regency Riau Province. The objectives of this research are:(1) to describe the social characteristics, economy and ecology of Subayang River environment at Tanjung Belit village (2) to analyze the shapes and the development of local communities wisdom associated with the preservation of the Subayang River ecosystem at Tanjung Belit village. The method used in this research is qualitaive method with qualitative approach including observation, interview guided by quissionare and documentation.Based on the result of the researh (1) social, economic and ecological with their customary forbidden forests and this prohibition hole is an event for the local community at Tanjung Belit village to keep the relationship betwen each other, prevent damage to the environmental of the forests and rivers and overcome forests damage and restoring environmental damage (2) shapes wisdom of local communities are ban on use putas, tuba and a stun, the ban on cutting tress, use of simple technology in clearing and opening and closing the prohibition hole. Key words: The wisdom of Local Communities, Ecosystems, Subayang River